2023
DOI: 10.3389/fnut.2022.1077452
|View full text |Cite
|
Sign up to set email alerts
|

Healthy dietary patterns, foods, and risk of glioma: A systematic review and meta-analysis of observational studies

Abstract: BackgroundAccumulating epidemiological evidence has shown the favorable associations between healthy dietary patterns and risk of glioma, although the results remain inconclusive.ObjectiveWe therefore carried out a systematic review and meta-analysis to summarize the evidence from previous published studies, and to clarify the effects of healthy dietary patterns, typical healthy foods on glioma.MethodsPubMed, Web of Science, CNKI, and Wan fang data were searched from inception up to September 2022 for eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Emerging research suggests potential links between certain dietary components and glioblastoma risk. [10] In essence, the global distribution of glioblastoma involves a complex interplay of genetic, environmental, and health factors. Unraveling these complexities is essential to advancing our knowledge of glioma epidemiology and ultimately improving prevention and treatment strategies on a global scale.…”
Section: Epidemiology and Classification Of Gliomasmentioning
confidence: 99%
“…Emerging research suggests potential links between certain dietary components and glioblastoma risk. [10] In essence, the global distribution of glioblastoma involves a complex interplay of genetic, environmental, and health factors. Unraveling these complexities is essential to advancing our knowledge of glioma epidemiology and ultimately improving prevention and treatment strategies on a global scale.…”
Section: Epidemiology and Classification Of Gliomasmentioning
confidence: 99%
“…Meta-analyses were performed to show the weighted effect size for homogenous comparisons when required metrics could be calculated in ≥ 3 studies according to previous studies [27,28]. The analysis was completed by Revman 5.4.1 and Rstudio software [29].…”
Section: Data Analysis and Levels Of Evidencementioning
confidence: 99%
“…The heterogeneity was evaluated by Cochran's Q and I 2 statistics tests. The fixed-effects model was selected when the heterogeneity was acceptable with p > 0.10 and I 2 < 50%; otherwise, a random-effects model was fitted [27]. Publication bias was displayed by funnel plots and Egger's test [23,27].…”
Section: Data Analysis and Levels Of Evidencementioning
confidence: 99%
“…In a combined analysis of 3 large prospective studies in the UK and US revealed a weak association between adherence to healthy dietary patterns, as measured by the dietary approaches to stop hypertension (DASH) eating plan, alternate Mediterranean diet and Alternative Healthy Eating Index (AHEI), and increased risk of glioma; however, these associations were generally null after excluding the first 5 years of follow-up [ 13 ]. The findings of a meta-analysis showed that following a healthy diet and consuming more vegetables and fruits was associated with reduced risk of glioma, but the findings regarding the consumption of whole grains, fresh fish, dairy products and nuts were not significant [ 14 ].…”
Section: Introductionmentioning
confidence: 99%